2021
DOI: 10.1029/2020jc016460
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Numerical Simulations of Internal Tides in the Angolan Upwelling Region

Abstract: Tropical eastern boundary upwelling systems are characterized by rich marine ecosystems (Carr & Kearns, 2003). They undergo strong intraseasonal to interannual variability dominantly associated with equatorial forcing and are often subject to intense hypoxia (e.g.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…Other factors such as the strength of stratification and mixing might play a role as well. A recent modeling study showed that the tidal energy available for mixing at the Angolan shelf is similar throughout the year, albeit the resulting mixing is more efficient during periods of shallow thermocline (Zeng et al, 2021…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other factors such as the strength of stratification and mixing might play a role as well. A recent modeling study showed that the tidal energy available for mixing at the Angolan shelf is similar throughout the year, albeit the resulting mixing is more efficient during periods of shallow thermocline (Zeng et al, 2021…”
Section: Discussionmentioning
confidence: 99%
“…It strengthens the seasonal downwelling in February and October and weakens the upwelling in June/July. The main upwelling season of Angola is in July-September (Kopte et al, 2017;Ostrowski et al, 2009;Zeng et al, 2021). This upwelling signal is again strengthened in its later phase by the upwelling wave of the phase-locked 120-day oscillations peaking in August/September.…”
Section: Impacts On the Sst Variabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…Meteorologically, the SETA region is situated on the northeastern flank of the South Atlantic Subtropical High (SASH) and therefore, the wind pattern is influenced by the southeast trades (Peterson and Stramma, 1991). In the northern part of the SETA region the mainly southerly wind is considerably weak (Risien et al, 2004;Fennel et al, 2012;Lübbecke et al, 2019;Zeng et al, 2021). Besides, in austral winter when SSTs are lowest, the upwelling favorable winds are weakest and thus, the shallowing of the thermocline occurring during that part of the year is not wind-driven.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, enhanced biological productivity off Angola in austral winter is mainly associated with the propagation of an upwelling CTW (e.g., Ostrowski et al, 2009;Rouault, 2012;Lübbecke et al, 2019). Mixing dominantly induced by internal tides (Zeng et al, 2021) transfers the CTW upwelling signal toward the surface to further modulate near coastal SST (Imbol Koungue and Brandt, 2021) and transport nutrients upward into the euphotic zone.…”
Section: Introductionmentioning
confidence: 99%